Phenomenology is not Phenomenalism. Is there such a thing as phenomenology of sport? - Jan Halák; Ivo Jirásek; Mark Stephen Nesti (Palacký University Olomouc, 2014)
Background: The application of the philosophical mode of investigation called "phenomenology" in the context of sport. Objective: The goal is to show how and why the phenomenological method is very often misused in sport-related research. Methods: Interpretation of the key texts, explanation of their meaning. Results: The confrontation of concrete sport-related texts with the original meaning of the key phenomenological notions shows mainly three types of misuse - the confusion of phenomenology with immediacy, with an epistemologically subjectivist stance (phenomenalism), and with empirical research oriented towards objects in the world. Conclusions: Many of the discussed authors try to take over the epistemological validity of phenomenology for their research, which itself is not phenomenological, and it seems that this is because they are lacking such a methodological foundation. We believe that an authentically phenomenological analysis of sport is possible, but it must respect the basic distinctions that differentiate phenomenology from other styles of thinking.